China Wheat Middlemen Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
China wheat middlemen survey is the study of Chinese middlemen in the wheat value chain in the province of Hena. These data allow us to quantify the extent of food loss in the middlemen level using consistent approaches that are comparable across commodities and regions. They also enable us to characterize the nature of food loss, specifically the production stages and the particular processes at which loss is incurred.